ISSUES OF WIDE IMPLEMENTATION OF FINANCIAL TECHNOLOGIES IN THE GLOBAL FINANCIAL MARKET - Abduraximova Dilora Karimovna (Journal Park Publishing, 2023)
In the last century, financial technologies have been widely introduced to develop the market of banking products in the world. Their appearance changed not only the banking systems of countries, but also the architecture of the financial market. The article analyzes the scope of implementation and use of innovative banking technologies in different regions of the world.
Keywords: banking innovations, financial technologies, banking services market, remote banking services, digital banks.